Structural and property changes of starch derivatives under microwave field: A review - Zhao, Yingting; Tu, Dongkun; Wang, Danni; Xu, Jingxin; Zhuang, Weijing; Wu, Fuhan; Tian, Yuting (International journal of biological macromolecules, 2024)
Native starches are commonly modified for desired properties because of their limited applications. Among various modifications, microwave irradiation has been gaining strong interests and becoming a focal area to transform starch during the last few years. Such interests reside in microwave irradiation's high heating rates, lesser extent of loss in nutritional qualities, and so on when compared with other approaches. This review summaries the effects of microwave field on the structural (e.g. morphology characteristic, lamellae structure, crystallinity, and molecular structure) and physicochemical properties (e.g. pasting properties and gelatinization) of naturally existing starch derivatives. Different microwave-assisted chemical derivatizations can directly or indirectly affect starch structure from the macroscopic to the microscopic level, thereby resulting in various functionalities. Moreover, conventional starch modification processes can be optimized by applying microwave irradiation to obtain modified starch with high degree of substitution and low viscosity. The future research will help to better understand the structural changes of microwave-assisted starch chemical derivatization and thereby creating a wide range of functionalities. •Microwave irradiation is a useful way to manipulate starch modification.•Schematic diagrams of microwave assisted starch chemical modification are shown.•Changes in starch structure from morphology to molecular structure are discussed.•Changes in pasting and gelatinization of starch derivatives are discussed.